2005
DOI: 10.3200/aeoh.60.2.86-95
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution in Rural China: Cooking Fuels, Stoves, and Health Status

Abstract: Solid fuels are a major source of indoor air pollution, but in less developed countries the short-term health effects of indoor air pollution are poorly understood. The authors conducted a large cross-sectional study of rural Chinese households to determine associations between individual health status and domestic cooking as a source of indoor air pollution. The study included measures of health status as well as measures of indoor air-pollution sources, such as solid cooking fuels and cooking stoves. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 3 publications
0
35
0
3
Order By: Relevance
“…WHO (2002) also reported 2.2-2.5 million annual deaths in developing countries due to indoor air pollution caused by ignition of rural sources of energy. Indoor pollution in developing countries has been gaining more attention recently (Balkrishnan et al 2002;Smith and Mehta 2003;Bhargava et al 2004;Smith et al 2004;Peabody et al 2005;Naeher et al 2007). Studies on health impact of indoor air pollution show prevalence of respiratory diseases such as chronic obstructive pulmonary disease, asthma, chronic bronchitis, and acute respiratory infections in all sexes and age groups (WHO Europe 1997;Robin et al 1996;Smith et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…WHO (2002) also reported 2.2-2.5 million annual deaths in developing countries due to indoor air pollution caused by ignition of rural sources of energy. Indoor pollution in developing countries has been gaining more attention recently (Balkrishnan et al 2002;Smith and Mehta 2003;Bhargava et al 2004;Smith et al 2004;Peabody et al 2005;Naeher et al 2007). Studies on health impact of indoor air pollution show prevalence of respiratory diseases such as chronic obstructive pulmonary disease, asthma, chronic bronchitis, and acute respiratory infections in all sexes and age groups (WHO Europe 1997;Robin et al 1996;Smith et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…As a result, HAP associated with solid fuels is estimated to be the largest single environmental risk contributor and ranks sixth among all risk factors examined for bad health in China [6], resulting in over half a million premature deaths annually [7]. At the same time, although a relatively large body of epidemiological and environmental literature examines the effects of HAP on health in parts of China [6,8,9,10,11,12,13,14,15], no studies assess this risk using nationally representative data and a longitudinal setting. Consequently, the evidence on HAP and health in China as a whole is scant, often narrowly focused (i.e., on certain provinces or cities) and usually based on cross-sectional analyses with limited generalizability and little ability to address confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Chinese people suffer severe health problems from air pollution. [2] It was reported that in China, infection of the lower respiratory tract ranked 8 among the 10 leading causes of death, accounting for 3% of total mortality, while indoor and outdoor air pollution ranked 4 and 7 respectively in 2001. [3] The total contribution of air pollution to the deaths was as high as 8.4%.…”
Section: Introductionmentioning
confidence: 99%